Spillovers from U.S. Monetary Policy Normalization on Brazil and Mexico's Sovereign Bond Yields - Goes, Carlos (IMF Working Papers; Working Paper, 2017)
This paper examines the transmission of changes in the U.S. monetary policy to localcurrency sovereign bond yields of Brazil and Mexico. Using vector error-correction models, we find that the U.S. 10-year bond yield was a key driver of long-term yields in these countries, and that Brazilian yields were more sensitive to U.S. shocks than Mexican yields during 2010-13. Remarkably, the propagation of shocks from U.S. long-term yields was amplified by changes in the policy rate in Brazil, but not in Mexico. Our counterfactual analysis suggests that yields in both countries temporarily overshot the values predicted by the model in the aftermath of the Fed's 'tapering' announcement in May 2013. This study suggests that emerging markets will need to contend with potential spillovers from shifts in monetary policy expectations in the U.S., which often lead to higher government bond interest rates and bouts of volatility.